2019
DOI: 10.1016/j.gexplo.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reclamation effort on the recovery of ecosystem functions of a tropical degraded serpentinite dump site

Abstract: Surface mining or other disturbing operations on ultramafic outcrops degrade soil conditions and decrease major ecosystem functions in those habitats. Human disturbances exacerbate the harsh conditions of some ultramafic soils, making recovery more difficult. Recovery of ecosystem functions of disturbed areas may vary from passive to active reclamation measures, depending on the starting situation, available resources and expected outcomes. In this study, three treatments (topsoil application, topsoil + non-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The study sites of Ata et al (2016) in Surigao and Zambales are mined areas disturbed by mining activities, planted with exotic species, and protected from fire. Several papers proved that natural colonization is faster if there are no exotic species planted in the area (Quintela-Sabarís et al, 2019). On the other hand, the site for this study is part of the wooded grassland reported by De Alban (2009) which has been idle up to the time when the survey for this study was conducted.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The study sites of Ata et al (2016) in Surigao and Zambales are mined areas disturbed by mining activities, planted with exotic species, and protected from fire. Several papers proved that natural colonization is faster if there are no exotic species planted in the area (Quintela-Sabarís et al, 2019). On the other hand, the site for this study is part of the wooded grassland reported by De Alban (2009) which has been idle up to the time when the survey for this study was conducted.…”
Section: Discussionmentioning
confidence: 89%
“…This observation indicates that wildings of the three exotic species may not thrive in the sites in Mindoro. In serpentine grasslands, natives generally out-compete exotics (Harrison et al, 2020). Moreover, spontaneous growth of the native species will be better if there are no exotic species (Quintela-Sabarís et al, 2019) provided there are adjacent populations of native plants (Řehounková et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that in case of extremely anthropized soil-scenario a-cultivation of selected plants in nursery and planting would be necessary to obtain a good plant cover (average plant cover in MINE plots is around 48%), whereas in scenario b spontaneous plant colonization may be an effective strategy for revegetation (almost 100% of plant cover in FIRE plots). However, spontaneous revegetation is feasible only if plant populations are locally present to act as seed sources [63] and if alien species are absent [65].…”
Section: Implication In Revegetation Of Ultramafic Degraded Areasmentioning
confidence: 99%
“…The most frequent artefacts are: construction debris, mine spoil and industrial waste, but also technic hard material (e.g., asphalt and bitumen) and geomembranes (Lehmann, 2006). Technosols encompass a wide variety of situations and are strongly heterogeneous, notably in terms of level of anthropization (Blume, 1989;Morel, Chenu, & Lorenz, 2015;Nov ak, Balla, & Kamp, 2020;Quintela-Sabarís, 2019). It is therefore important to stress that Technosols are not only found in artificial land, and that soils in artificial land are not only Technosols.…”
Section: Introductionmentioning
confidence: 99%